Exogenous Cushing Syndrome: When do We Get the Benefit of Glucocorticoid Stress Dose? - Soelistijo, Soebagijo Adi; Gunawan, Hendra; Primasatya, Chandra Adi Irawan; Ariana, Audy Meutia; Mudjanarko, Sony Wibisono; Pranoto, Agung (Jurnal Penyakit Dalam Indonesia, 2020)
Exogenous cushing syndrome is the most common cushing syndrome found in clinical practice. Its most frequent etiology is the adverse effect of glucocorticoid therapy found in clinical practice or in the form of traditional medicine. The clinical manifestations of exogenous cushing syndrome are similar to the spontaneous counterpart, albeit with the presence of glucocorticoid consumption. We present a case series of exogenous cushing syndrome due to traditional medicine and glucocorticoid consumption with opportunistic infection as its initial manifestation. The first case did not need glucocorticoid supplementation while it was initiated in the second case. Comprehensive management of exogenous cushing syndrome should involve the decision of giving glucocorticoid stress dose, treatment to the underlying disease and education in order to prevent self-glucocorticoid consumption.